Size Dependent Heat Conduction in One-Dimensional Diatomic Lattices. (1st April 2016) - Shah, Tejal N.; Gajjar, P.N.
Abstract: We study the size dependency of heat conduction in one-dimensional diatomic FPU-β lattices and establish that for low dimensional material, contribution from optical phonons is found more effective to the thermal conductivity and enhance heat transport in the thermodynamic limit N → ∞. For the finite size, thermal conductivity of 1D diatomic lattice is found to be lower than 1D monoatomic chain of the same size made up of the constituent particle of the diatomic chain. For the present 1D diatomic chain, obtained value of power divergent exponent of thermal conductivity 0.428±0.001 and diffusion exponent 1.2723 lead to the conclusions that increase in the system size, increases the thermal conductivity and existence of anomalous energy diffusion. Existing numerical data supports our findings.